2011
DOI: 10.1111/j.1742-7843.2011.00767.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Analgesic Acetaminophen (Paracetamol) and its para‐Aminophenol Metabolite on Viability of Mouse‐Cultured Cortical Neurons

Abstract: Acetaminophen has been used as an analgesic for more than a hundred years, but its mechanism of action has remained elusive. Recently, it has been shown that acetaminophen produces analgesia by the activation of the brain endocannabinoid receptor CB1 through its para-aminophenol (p-aminophenol) metabolite. The objective of this study was to determine whether p-aminophenol could be toxic for in vitro developing mouse cortical neurons as a first step in establishing a link between acetaminophen use and neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…An interesting theory relating the MMR vaccine to ASD involves a proposed toxic reaction to the acetaminophen (paracetamol) administered to control fever following vaccination [25,106]. It has been proposed that acetaminophen may mediate oxidative stress and neurotoxicity in autism [107], and acetaminophen has been demonstrated to be toxic to developing mouse cortical neurons in vitro [108]. Table 2.…”
Section: Distribution Of Vaccine Types In Autism Versus Controlsmentioning
confidence: 99%
“…An interesting theory relating the MMR vaccine to ASD involves a proposed toxic reaction to the acetaminophen (paracetamol) administered to control fever following vaccination [25,106]. It has been proposed that acetaminophen may mediate oxidative stress and neurotoxicity in autism [107], and acetaminophen has been demonstrated to be toxic to developing mouse cortical neurons in vitro [108]. Table 2.…”
Section: Distribution Of Vaccine Types In Autism Versus Controlsmentioning
confidence: 99%
“…P-aminophenol is recognized to be involved in paracetamol nephrotoxicity [81,109]. More recently, P-aminophenol has been shown to produce a significant loss in mouse cortical neuron viability at therapeutic concentrations [12]. This suggests another possible pathway for a neurotoxic effect of paracetamol when the principle metabolic routes are exhausted.…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation found transcriptomic changes in full-genome human miRNA expression indicating, for the first time, immune modulating effects and oxidative stress responses to paracetamol even at low doses [10]. Studies in animals have shown paracetamol to induce apoptosis and neurotoxicity [11,12]. Several studies hypothesize increased apoptosis in the autistic brain [13-16].…”
Section: Introductionmentioning
confidence: 99%
“…While there are data from pharmacokinetics studies [12,13], the pharmacodynamics of paracetamol in neonates are poorly described. Allegaert et al [14] showed a reduction of pain after 20 mg/kg of paracetamol in preterm and term infants suffering from delivery trauma.…”
Section: Discussionmentioning
confidence: 99%